Degradation of a non-oxidizing biocide in circulating cooling water using UV/persulfate: Kinetics, pathways, and cytotoxicity. (February 2022) - Cui, Jinzhi; Cai, Shaokang; Zhang, Shurong; Wang, Guiqiao; Gao, Canzhu
Abstract: In industry, isothiazolinone (a mixture containing 5-chloro-2-methyl-4-isothiazolin-3-one (CMIT) and 2-methyl-4-isothiazolin-3-one (MIT), CMIT-MIT) as a non-oxidizing biocide is extensively used to control the growth of microorganisms in the circulating cooling water system, which potentially threatens the ecological environment and human health. In this work, the oxidative degradation of CMIT-MIT by UV/persulfate (PS) technology on a laboratory-scale was systematically investigated. The degradation of CMIT-MIT was greatly improved by UV/PS compared with only UV or oxidant. During the photolysis of 60 mg/L PS, the degradation rate and TOC mineralization rate of CMIT-MIT were 91% and 34.7%, respectively. The contributions of . OH and SO4 · − to CMIT-MIT degradation in the UV/PS system were estimated to be 0.93% and 32.12% respectively. The degradation rate of CMIT-MIT decreased slightly with the increase of pH. The presence of SO4 2− and NO3 − had no significant effect on the degradation of CMIT-MIT, while the presence of Cl − and CO3 2− inhibited the CMIT-MIT removal rate. The degradation pathways and three possible intermediates of CMIT-MIT were obtained. After degradation of CMIT-MIT by UV/PS process, the cytotoxicity decreased within 20 min, effectively indicating that UV/PS could be as a potential technology to remove the CMIT-MIT in water treatment. Graphical abstract: Image 1 Highlights: The removal rate and TOC mineralization degree of CMIT-MIT were 91% and 34.7% respectively in UV/PS process. The contributions of . OH and SO4 · − to CMIT-MIT degradation were 0.93% and 32.12% respectively. The cytotoxicity was weakened after degradation of CMIT-MIT by UV/PS process.